Measurement for Surface Tension of Aqueous Inorganic Salt - Wen, Jiming; Shi, Kaiyi; Sun, Qiunan; Sun, Zhongning; Gu, Haifeng (Frontiers in Energy Research, 2018)
Bubble columns are effective means of filtration in filtered containment venting systems. Here, the surface tension has a significant influence on bubble size distribution and bubble deformation, which have a strong impact on the behavior of the bubble column. The influence of aqueous inorganic compounds on the surface tension depends on the electrolytic activity, Debye length, entropy of ion hydration and surface deficiencies or excess. In this work the surface tensions of same specific aqueous solutions have been measured by different methods including platinum plate method, platinum ring method and maximum bubble pressure method. The measured surface tensions of both sodium hydroxide and sodium thiosulfate are less than that of water. As solution temperature ranges from 20 ℃ to 75 ℃, the surface tension of 0.5 mol/L sodium hydroxide solution decreases from 71 to 55 mN/m while that of 1 mol/L solution decreases from 60 to 45 mN/m. Similarly during the same temperature range, the surface tension of 0.5 mol/L sodium thiosulfate decreases from 70 to 38 mN/m and that of 1 mol/L sodium thiosulfate is between 68 and 36 mN/m. The analysis for the influence mechanism of aqueous inorganic on surface tension is provided. In addition, experimental results show that the surface tension of solid aerosol suspension liquid has no obvious difference from that of distilled water.